Review of water-based extraction techniques affecting the antioxidant activity of pomegranate peel - Farhana, R.; Suriani, Ni Luh; Sukor, R.; Izham, I.; Medihi, N. I.; Raseetha, S. (Rynnye Lyan Resources, 2025)
The demand in the agricultural sector is on the rise, which is indirectly linked to the accumulation of agricultural wastes via post-harvest operation, transportation, wholesale, retail, storage, processing and packaging, which occurs in the food supply chain has been one of the major challenges faced globally. Agricultural wastes contain diverse types of bioactive compounds, which can be further utilised for the enhancement of food values. In the present review, several water-based extractions were discussed including maceration, digestion, infusion, decoction, percolation, Soxhlet, hydrodistillation, steam-distillation, ultrasound-assisted and microwave-assisted extraction. The comparisons were based on the polyphenol content and antioxidant activities focussing on pomegranate peel (POMEP). This review discussed various polyphenol compounds found in POMEP (ellagic acid and punicalagin) that contributed to antioxidant activities. It was found that the acceptable limit of radical scavenging activities of POMEP was 65% in water-based extractions, respectively. POMEP revealed that water-based maceration, digestion, infusion, decoction, ultrasound-assisted and microwave-assisted extraction showed acceptable antioxidant activities. Therefore, water-based extractions portrayed great potential to be assimilated into the market based on their antioxidant potential and their non-toxic and environment-friendly characteristics. This review is important to food industries and stakeholders to further explore the possibilities of utilising fruit peels as functional food products.